Early modern stockings in museums in the Czech Republic - Odstrčilová, Sylvie (Archaeological Textiles Review, 2018)
Knitted stockings from six burials dating from 1576 to 1626 and three without clear dating were examined. All the stockings have fully shaped legs and triangular gussets bordered on all three sides with patterns of reverse loops, along which the foot was shaped by both decreases and increases. Right-leaning decreases were used mostly; left-leaning decreases were used only in some stockings, exclusively in the upper part of the gusset on the proper left side of the stocking. For increasing, only raised (row below lifted) increases were used. Their asymmetric position in several stockings shows that some of the early knitters understood an increase to be two loops knitted from one parent loop, and for some it was only an added loop. Instead of the usual method of picking up new loops for gussets, the heel flap selvedges were probably whipstitched in several stockings, and these sewn stitches were then used as the base for knitting the gussets. A comparison of the stockings from the Czech Republic to the stockings from the same period found in other European countries suggests the possibility of using a range of construction types for determining their provenance.